Information Security Education Across the Curriculum : 9th IFIP WG 11.8 World Conference, WISE 9, Hamburg, Germany, May 26-28, 2015, Proceedings - Bishop, Matt.; Miloslavskaya, Natalia; Theocharidou, Marianthi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 9th IFIP WG 11.8 World Conference on Security Education, WISE 9, held in Hamburg, Germany, in May 2015. The 11 revised papers presented together with 2 invited papers were carefully reviewed and selected from 20 submissions. They are organized in topical sections on innovative methods, software security education, tools and applications for teaching, and syllabus design.
Realism in Teaching Cyber security Research: The Agile Research Process -- Assurance Cases as a Didactic Tool for Information Security -- Cognitive Task Analysis Based Training for Cyber Situation Awareness -- A Cyber Security Multi Agency Collaboration for Rapid Response that Uses AGILE Methods on an Education Infrastructure -- Cyber security Through Secure Software Development -- Security Injections 2.0: Increasing Engagement and Faculty Adoption Using Enhanced Secure Coding Modules for Lower-Level Programming Courses -- The Use of Software Design Patterns to Teach Secure Software Design: An Integrated Approach -- Learn to Spot Phishing URLs with the Android No Phish App -- An Innovative Approach in Digital Forensic Education and Training -- On Experience of Using Distance Learning Technologies for Teaching Cryptology -- Reflections on the Ethical Content of the IT Honours Program Project Module -- Professional Competencies Level Assessment for Training of Masters in Information Security -- History of Cryptography in Syllabus on Information Security Training.
Keywords: Education; Computer security; Information Systems; Computers and Education; Systems and Data Security; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Educational Technology; Teaching and Teacher Education